Vitamin B1 ecophysiology of marine picoeukaryotic algae: Strain‐specific differences and a new role for bacteria in vitamin cycling. (9th January 2015) - Paerl, R. W.; Bertrand, E. M.; Allen, A. E.; Palenik, B.; Azam, F.
Abstract We confirmed multiple picoeukaryotic algae, Ostreococcus, Micromonas, and Pelagomonas spp., as thiamine (vitamin B1) auxotrophs in laboratory experiments with axenic cultures. Examined strains have half saturation growth constants (Ks) for B1 between 1.26 and 6.22 pmol B1 L−1, which is higher than reported seawater concentrations. Minimum B1 cell quotas for Ostreococcus and Micromonas spp. are high (2.20 × 10−8–4.46 × 10−8 pmol B1 cell−1) relative to other B1 auxotrophic phytoplankton, potentially making them B1 rich prey for zooplankton and significant B1 reservoirs in oligotrophic marine habitats. Ostreococcus and Micromonas genomes are nonuniformly missing portions of the B1 biosynthesis pathway. Given their gene repertoires, Ostreococcus lucimarinus CCE9901 and Ostreococcus tauri OTH95 are expected to salvage B1 from externally provided 4‐methyl‐5‐thiazoleethanol (HET) and 4‐amino‐5‐hydroxymethyl‐2‐methylpyrimidine (HMP). However, in culture, neither could use HET plus HMP instead of B1, highlighting current limitations of genome‐based prediction of B1 salvaging by picoeukaryotic algae. HMP and phosphorylated B1 use varied amongst tested strains and notably all Prasinophytes tested could not use HMP. B1‐limited O. lucimarinus CCE9901 could not grow on added thiamine diphosphate (TDP), a phosophorylated B1 form. However, in co‐culture with Pseudoalteromonas sp. TW7, a bacterium known to exhibit phosphatase activity, O. lucimarinus CCE9901 exhibited increased growth following TDP additions. This demonstrates that bacteria influence vitamin B1 availability beyond de novo synthesis and consumption; they can also serve as conduits that chemically alter, but not completely degrade or retain B1 analogs (e.g., TDP), and make them accessible to a broader range of microbes.